PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, DAN KEPERCAYAAN TERHADAP KEPUASAN ORANG TUA PESERTA DIDIK PADA TK KARTIKA MANDALA DENPASAR - I Made Dipa Arigata; Ni Putu Nita Anggraini; Pande Ketut Ribek (VALUES, 2022)
Kindergarten as an educational institution that develops early childhood skills, of course, must pay attention to the satisfaction of parents who send their children to Kartika Mandala Kindergarten. Because parents' satisfaction with the results of education in kindergarten as a provider of educational services will later determine the number of new student admissions. This study aims to examine and obtain empirical evidence of the effect of service quality, price perception, and trust on the satisfaction of parents of students at Kartika Mandala Kindergarten Denpasar. The population in this study was parents of students at Kartika Mandala Kindergarten in the last 5 years, from 2016 to 2020 a total of 277 students. The sampling technique used proportionate stratified random sampling so that 56 people were used as samples. The analytical tool used is multiple linear analysis, classical assumption test, t test, and F test. The results of this study indicate that service quality, price perception, and trust have a positive and significant effect on the satisfaction of parents of students at Kartika Mandala Kindergarten Denpasar. It is recommended to Kartika Mandala Kindergarten Denpasar to further improve the handling of complaints from parents of students, which can be used as input and suggestions to realize better services in the future.